Microsurgical Scalp Reconstruction in the Elderly: A Systematic Review and Pooled Analysis of the Current Data. Issue 3 (March 2015) - Sosin, Michael; Schultz, Benjamin D.; De La Cruz, Carla; Hammond, Edward R.; Christy, Michael R.; Bojovic, Branko; Rodriguez, Eduardo D.
Abstract : Background: Microvascular reconstruction is the mainstay of treatment in complex scalp defects. The rate of elderly patients requiring scalp reconstruction is increasing, but outcomes in elderly patients are unclear. The purpose of this study was to systematically review the literature pertaining to free tissue transfer for scalp reconstruction in patients older than 65 years to compare outcomes among different free flaps and determine the safety profile of treatment. Methods: A systematic review of the available literature of patients undergoing microvascular scalp reconstruction was completed. Details for patients 65 years and older were extracted and reviewed for data analysis. Results: A total of 45 articles (112 patients) were included for analysis. Mean age of the patients was 73.3 ± 6.3 years (men, 69.4 percent; women, 23.4 percent; not reported, 7.2 percent). Mean flap size was 598 cm 2 (range, 81 to 2500 cm 2 ). The mean age of patients developing a complication was 72.8 ± 6.4 years and patients that did not develop a complication was 73.4 ± 5.5 years ( p = 0.684). Overall, periprocedural mortality was 0.9 percent. Flap failures occurred in two cases (1.8 percent). The overall complication rate was 22.3 percent ( n = 25). Complications by flap type varied without reaching statistical significance. Conclusions: Microvascular reconstruction in complex scalp defects is associated with successful outcomes, and chronologic age does not increase mortality or catastrophic flap complications. The most common flaps used to repair scalp defects are anterolateral thigh and latissimus dorsi, but a superior flap type could not be identified. Abstract : Coding Perspective for this article is on page 864.